Current density distribution in an HT-PEM fuel cell with a poly (2, 5-benzimidazole) membrane. (11th January 2021) - Yu, Mingfu; Sun, Hong; Zhang, Tianyu; Li, Qiang; Li, Jie; Zhang, Xiaochen
Abstract: High-temperature proton exchange membrane (HT-PEM) fuel cells were more useable than traditional low-temperature proton exchange membrane fuel cells. To investigate the current density distribution in a single HT-PEM fuel cell with a poly (2, 5-benzimidazole) membrane, a modified current distribution measuring device was developed. This device included not only a current distribution measuring gasket to collect local current but also a segmented gas diffusion layer (GDL) to hinder electron transfer in the GDL along the gas flow direction. The effects of this device installation configuration and operating conditions on the current density distribution were analyzed. One of the important findings was that proton transfer along an in-plane direction in the membrane and electron transfer along an in-plane direction in the GDL really occur in HT-PEM fuel cells. These results were very helpful for the optimization of the flow field and operating parameters of the HT-PEM fuel cells. Highlights: A modified current distribution measuring device was developed. Proton transfer along in-plane direction in the membrane occurs in HT-PEM fuel cells. The current density decreases along the reactant gas flow direction. Optimal hydrogen flow rate improves the performance of the HT-PEM fuel cell.